Effectiveness of Ozonization on Total Vibrio Bacteria and Viruses in Sea Worms (Nereis sp.) as Natural Feed of Vannamei Shrimp (Litopenaeuse vannamei) - Frida Alifia; Evi Nursanti (Indonesian Journal of Coastal and Marine Studies, 2025)
The total bacteria and viruses in sea worms as vannamei shrimp mother feed are greatly influenced by the ozonization treatment in worms. The purpose of this study is to determine the effect of ozonation on the number of vibrio bacteria and viruses in sea worms. This research was carried out at the CV Laboratory. Source Bangka Hatchery, Mapur Village, Riau Silip District, Bangka Regency, Bangka Belitung Province. The research method used is mixed methods with experimental testing procedures designed with a Complete Acal Design (RAL) with 4 treatments with 3 replicas each which aims to determine the effect of ozonation on the number of vibrio bacteria and viruses in sea worms. The results showed that ozonization treatment had a significant influence on the microbiological quality of sea worms, especially in terms of total Vibrio bacteria and the level of viral contamination. The ozonization treatment has been proven to be able to reduce the total number of Vibrio bacteria present in the body of sea worms. Vibrio bacteria are a group of microorganisms that are often associated with the risk of disease in humans and aquatic animals. This decrease in the number of bacteria shows that ozone can be an effective antimicrobial agent in suppressing the growth and spread of pathogenic bacteria. In addition, ozonization also affects the level of viral contamination in sea worms. Ozone is known as a powerful oxidizer that can damage the structure of proteins and nucleic acids in viruses, thereby reducing the viability and infectivity level of viruses contained in sea worm tissues. The results showed a marked difference between the control group and the ozonized treatment group, where the treatment group showed significantly lower levels of virus contamination.